(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article acguuints vith essence. functions. bases and organizational forms of extracurricular and out-of-school employments, thai is one of substantial elemenis of structure of pedagogical knowledges of the Polish teachers.